2016
DOI: 10.1080/09712119.2016.1206902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo injection of threonine on hatchability, intestinal morphology, and somatic attributes in Japanese quail (Coturnix japonica)

Abstract: View related articles View Crossmark data Citing articles: 4 View citing articles Effects of in ovo injection of threonine on hatchability, intestinal morphology, and somatic attributes in Japanese quail (Coturnix japonica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…These results, along with the result of intestinal weight, suggested that IOF of Arg solution mainly promoted the growth performance of early‐stage chicks from 1 to 21 days. Previous studies also reported that the effects of IOF nutrients might be limited, and that positive effects could be attenuated after the birds gained access to feed posthatch . Besides, Tahmasebi and Toghyani reported that IOF of Arg solution significantly increased chick BW at 24 days posthatch and FI during 1–42 days compared with the control group .…”
Section: Discussionmentioning
confidence: 91%
“…These results, along with the result of intestinal weight, suggested that IOF of Arg solution mainly promoted the growth performance of early‐stage chicks from 1 to 21 days. Previous studies also reported that the effects of IOF nutrients might be limited, and that positive effects could be attenuated after the birds gained access to feed posthatch . Besides, Tahmasebi and Toghyani reported that IOF of Arg solution significantly increased chick BW at 24 days posthatch and FI during 1–42 days compared with the control group .…”
Section: Discussionmentioning
confidence: 91%
“…A previously described method to prepare samples for histomorphometry analysis was used ( Kermanshahi et al., 2017a ). Briefly, the jejunal content was flushed out with physiological saline and a section of 2 cm of the tissue (midway between the Meckel's diverticulum and the entrance of the bile ducts) was stored in 10% formalin for 48 h followed by paraffin embedding cut to a thickness of 5 μm using a microtome.…”
Section: Methodsmentioning
confidence: 99%
“…Embryonic development is affected by many factors, including egg nutrition, temperature, and humidity (Dymond et al, 2013;Noiva et al, 2014;Yildirim and Yetisir, 2004). Previous reports have indicated that the changes in egg nutrition affect the embryonic development and health (Bhattacharyya et al, 2018;Kermanshahi et al, 2017). Other researchers have shown that restricting maternal nutrition affects the development of embryos (Prezotto et al, 2016;Raja et al, 2016).…”
Section: Introductionmentioning
confidence: 99%